Hydration gradients drive lipid self-segregation - Nikol Labecka; Jenny M. Andersson; Emma Sparr; Kevin Roger (Proceedings of the National Academy of Sciences, 2026)
Evaporation from a multicomponent aqueous mixture not only establishes a hydration gradient but may also lead to composition gradients in the other components. Here, we show that such a gradient induces a strong segregation between two phospholipids that differ only in the saturation of their acyl chains. Using high-resolution confocal Raman microscopy combined with small- and wide-angle X-ray scattering, we simultaneously resolve local composition and structure along the evaporation direction. We find that the saturated phospholipid, dipalmitoyl phosphatidylcholine (DPPC), accumulates near the air–liquid interface, while the unsaturated phospholipid, dioleoyl phosphocholine (DOPC), is displaced toward a more hydrated intermediate region, resulting in a complete inversion of their initial proportions. This nonmonotonic lipid gradient reflects the different water swelling capacities of the L β′ and L α lamellar phases favored by DPPC and DOPC, respectively. Despite the system being out of equilibrium, the segregation is quantitatively captured by a description based on local equilibrium chemical potentials and multicomponent diffusion with cross-coupling. Our findings identify hydration gradients as a robust driver of lipid segregation and establish a general framework for predicting transport and organization in evaporating soft-matter systems.